Detection of Symptomatic Carotid Plaque Using Source Data from MR and CT Angiography: A Correlative Study - Gupta, Ajay; Baradaran, Hediyeh; Mtui, Edward E.; Kamel, Hooman; Pandya, Ankur; Giambrone, Ashley; Iadecola, Costantino; Sanelli, Pina C. (Cerebrovascular diseases (Basel, Switzerland), 2015)
Background: Carotid plaque MRI has been a useful method to characterize vulnerable atherosclerotic plaque elements. Recent investigations have suggested that source images from CT angiography (CTA) and MR angiography (MRA) can identify the simple high-risk features of symptom-producing carotid artery plaque. We studied the correlation and relative diagnostic accuracies of CTA and MRA source images in detecting symptomatic carotid artery plaque. Methods: Subjects were eligible if they had carotid stenosis between 50 and 99% and had MRA and CTA exams performed within 10 days of one another. We measured the soft (non-calcified) plaque and hard (calcified) plaque thickness on CTA axial source images and intraplaque high-intensity signal (IHIS) on 3D-time-of-flight MRA source images in subjects. We assessed whether a correlation existed between increasing CTA soft plaque thicknesses and the presence of MRA IHIS using the Student's t-test. We calculated the differences in sensitivity and specificity measures of CTA and MRA source-imaging data with the occurrence of recent ipsilateral stroke or transient ischemic attack (TIA) as the reference standard. We also performed logistic regression analyses to evaluate the predictive strength of plaque showing both IHIS and increased CTA soft plaque thickness in predicting symptomatic disease status. Results: Of 1994 screened patients, 48 arteries met the final inclusion criteria with MRA and CTA performed within 10 days of one another. The mean and median time between CTA and MRA exams were 2.0 days and 1 day, respectively. A total of 34 of 48 stenotic vessels (70.8%) were responsible for giving rise to ipsilateral stroke or TIA. CTA mean soft plaque thickness was significantly greater (4.47 vs. 2.30 mm, p < 0.0001) in patients with MRA-defined IHIS, while CTA hard plaque thickness was significantly greater (2.09 vs. 1.16 mm, p = 0.0134) in patients without MRA evidence of IHIS. CTA soft plaque thickness measurements were more sensitive than MRA IHIS (91.2 vs. 67.6%, p = 0.011) in detecting symptomatic plaque, while differences in specificity were not significantly different (p = 0.1573). In the subset of patients with both IHIS on MRA and plaque thickness >2.4 mm on CTA, the odds ratio of detecting symptomatic plaque, corrected for stenosis severity, was 45.3 (p < 0.0005). Conclusions: Unprocessed source images from CTA and MRA, which are routinely evaluated for clinical studies demonstrate the highly correlated presence of IHIS and increasing soft plaque thickness. In particular, plaque that shows high-risk features on both MRA and CTA are very strongly associated with symptom-producing carotid plaque. With further validation, such techniques are promising practical methods of extracting risk information from routine neck angiographic imaging.